Clinical Characteristics Associated with Suicide Attempts in Clinical Settings: A Comparison of Suicidal and Non-Suicidal Depressed Inpatients - Gramaglia, Carla; Feggi, Alessandro; Bergamasco, Paola; Bert, Fabrizio; Gattoni, Eleonora; Marangon, Debora; Siliquini, Roberta; Torre, Eugenio; Zeppegno, Patrizia (Frontiers in Psychiatry, 2016)
Introduction Psychiatric management of inpatients with suicidal behavior involves psychiatrists and psychiatric nurses. Specific precautions should be adopted: observation on a one to one basis with the cooperation of qualified nurses and accommodating the patient in a room close to the infirmary is usually recommended. An ongoing assessment of suicidal risk is warranted to check the response to treatment over time. Aim To compare the severity of depressive symptoms in depressed inpatients admitted after an attempted suicide and in depressed inpatients admitted for any other reason; to assess the severity of attempted suicide and the management of suicidal risk in the clinical setting. Material and method We divided the sample in two subgroups: patients with a diagnosis of depression admitted for a current suicide attempt and depressed patients without a current suicide attempt. Socio-demographic and clinical features were gathered; assessment included the Montgomery-Asberg Depression Rating Scale (MADRS) and the Nurses’ Global Assessment of Suicide Risk (NGASR). Results 46 patients were recruited in a 1-year period and were eligible for our study: 20 had been admitted to the hospital after attempting suicide, while the other 26 had not attempted suicide and were admitted for other reasons related to their depression. The multivariate analysis yielded a statistically significant correlation between the use of antidepressants and current suicide attempt. The occurrence of suicidal attempt was not significantly related to the severity of depressive symptoms. In the current suicide attempters subgroup, NGASR suicide risk levels at discharge were significantly lower than those measured at admission. Current suicide attempters had a higher number of suicide attempts in their clinical history, compared to the other group. Conclusion We found no significant correlation among psychiatric diagnosis, severity of depressive symptoms and current suicide attempt. Antidepressant therapy was found to play the role of protective factor for suicide attempts. History of suicide attempts was one of the major predictor for reattempted suicide. A more thorough understanding of the complex phenomenon of suicide and of the reasons underlying suicidal behaviors is warranted.